Associations between frequency of cigarette and alternative tobacco product use and depressive symptoms: A longitudinal study of young adults. (December 2019) - Marsden, David G.; Loukas, Alexandra; Chen, Baojiang; Perry, Cheryl L.; Wilkinson, Anna V.
Abstract: The association between cigarette use and depression has been documented in many studies. Fewer studies have examined other tobacco products such as electronic cigarettes (e-cigarettes) and hookah that are used by young adults. This study examined whether increased frequency of use of these products was associated with depressive symptoms in a cohort of n  = 5236 Texas college students followed from 2014 to 2017. To analyze the longitudinal data, a hierarchical model was used. Model results showed that increased frequency of single product use of cigarettes, refillable e-cigarettes and hookah was associated with depressive symptoms. Refillable and disposable e-cigarettes were examined separately and results did not provide evidence of a different association for each type of e-cigarette when cigarettes were not also used. Dual use of cigarettes with another product was also examined. Dual use was associated with higher depressive symptoms for most product combinations. However, infrequent dual use of disposable e-cigarettes and cigarettes may not be associated with depressive symptoms. Suggestions for further research are included. Highlights: This study examined the association between frequency of product use and depressive symptoms for 6 tobacco products. Frequency of single product use was associated with depressive symptoms for cigarettes, refillable e-cigarettes & hookah. Dual use was associated with higher depressive symptoms than single product use for most product combinations. Infrequent dual use of disposable e-cigarettes & cigarettes was not associated with higher depressive symptoms.